High-level production and aggregation of hepatitis B surface antigen in transgenic tobacco seeds - Abel Hernández; Alina López; Yanaysi Ceballo; Lissy Rosabal; Yamilka Rosabal; Kenia Tiel; Marlene Pérez; Ernesto M González; Osmani Ramos; Gil Enríquez (Biotecnología Aplicada)
The hepatitis B surface antigen (HBsAg) has been successfully produced in tobacco leaves, potato tubers and banana fruits, but at a rather low yield. Plant seeds are well suited for the accumulation, long-time storage and preservation of recombinant proteins with pharmaceutical interest, including antigens for prophylactic or therapeutic vaccines. In this work, we assessed the efficacy of the tissue-specific phaseolin promoter in driving the expression of the HBsAg gene in tobacco seeds. Two binary constructs were designed to synthesize this antigen fused or not to the KDEL motif for protein targeting to the endoplasmic reticulum. Tobacco plants were transformed via Agrobacterium tumefaciens using each construct. The highest yield (2.2 µg of the recombinant protein per gram of seed) was achieved by a transgenic line carrying the HBsAg gene without the KDEL fusion. The heterologous antigen aggregated properly forming particles that could be determined using an immunoenzymatic assay based on monoclonal antibody which recognizes the immunodominant epitope a of HBsAg, although seed-derived antigens sedimented slightly faster than the one produced in Pichia pastoris yeast. The HBsAg-expressing tobacco seeds could constitute a novel alternative source for the cost-effective production of the antigen.